Transmission pathways of campylobacter spp. at broiler farms and their environment in Brandenburg, Germany - Reichelt, Benjamin; Szott, Vanessa; Epping, Lennard; Semmler, Torsten; Merle, Roswitha; Roesler, Uwe; Friese, Anika (Frontiers in Microbiology, 2022)
Broiler meat is widely known as an important source of foodborne Campylobacter jejuni and Campylobacter coli infections in humans. In this study, we thoroughly investigated transmission pathways that may contribute to possible Campylobacter contamination inside and outside broiler houses. For this purpose we carried out a comprehensive longitudinal sampling approach, using a semi-quantitative cultivation method to identify and quantify. transmissions and reservoirs of Campylobacter spp. Three german broiler farms in Brandenburg and their surrounding areas were intensively sampled, from April 2018 until September 2020. Consecutive fattening cycles and intervening downtimes after cleaning and disinfection were systematically sampled in summer and winter. To display the potential phylogeny of barn and environmental isolates, whole genome sequencing (WGS) and bioinformatics analyses were performed. Results obtained in this study showed very high Campylobacter prevalence in 51/76 pooled feces (67.1%) and 49/76 boot swabs (64.5%). Average counts between 6.4 to 8.36 log10MPN/g were detected in pooled feces. In addition, levels of 4.7 and 4.1 log10MPN/g were detected in boot swabs and litter, respectively. Samples from the barn interior showed mean Campyloacter values in swabs from drinkers 2.6 log10MPN/g, walls 2.0 log10MPN/g, troughs 1.7 log10MPN/g, board 1.6 log10MPN/, ventilation 0.9 log10MPN and 0.7 log10MPN/g for air samples. However, Campylobacter was detected only in 7/456 (1.5%) of the environmental samples (water bodies, puddles or water-filled wheel tracks) (average of 0.6 log10MPN/g). Furthermore, WGS showed recurring Campylobacter genotypes over several consecutive fattening periods, indicating that Campylobacter genotypes persist in the environment during downtime periods. However, after cleaning and disinfection of the barns, we were unable to identify potential sources in the broiler houses. Interestingly, alternating Campylobacter genotypes were observed after each fattening period, also indicating sources of contamination from the wider environment outside the farm. Therefore, the results of this study suggest that a potential risk of Campylobacter transmission may originate from present environmental sources (litter and water reservoirs). However, the sources of Campylobacter transmission may vary depending on the operation and farm environmental conditions.